Implementasi Manajemen Peningkatan Mutu Berbasis Madrasah Pada MINU Pucang Bertaraf Internasional - Moch. Zakki Mubarok; Niswatin (IAI Al Khoziny Buduran Sidoarjo, 2021)
This study aims to determine the implementation of madrasah-based quality improvement management at international standard madrasah at MINU Pucang Sidoarjo, this study uses a qualitative approach. As for the results of the study, it is known that the concept of international standard madrasa management quality in its implementation goes through the following stages: The concept of institutional management, supporting factors, weaknesses, planning stages, Doing, checking, acting. From these stages, madrasah are produced that are able to compete and are competent and attract the interest of parents and students to be able to study at MINU Pucang Sidoarjo.